Spatial heterogeneity of biological traits and effects on fisheries management based on the assumption of a single stock. The case of the common hake (Merluccius gayi) in Chile - Canales, Cristian M.; Sánchez, Nazareth; Adasme, Nicolás A. (Frontiers in Marine Science, 2023)
Understanding the spatial structure of fishing resource stocks is a fundamental aspect for the management and development of sustainable and productive fisheries. However, this aspect is usually simplified under the assumption of a stock unit, which assumes biologically similar and spatially homogeneous individuals, regardless of the real ranges and characteristics of their distribution. The persistence of geographic patterns in the biological traits of species suggests the spatial structuring of a population, a highly relevant aspect in stock assessment, calculation of Biological Reference Points (BRP), and management of fishing resources. In this work, the spatial heterogeneity of the biological traits of common hake (Merluccius gayi) from off-central Chile is modeled. Considering four reference zones, biological data collected over 26 years of monitoring fisheries and acoustic surveys is analyzed. The findings allow to biologically differentiate these areas whose main characteristics are the increase from north to south in the condition factor, gonad weight, and size at maturity. The Spawning Potential Ratio (SPR), fishing mortality, and BRP are calculated. Exploratorily, if these areas were considered closed subpopulations, results show that overexploitation is not a characteristic of all hake fishing areas, and that not considering the heterogeneity of biological traits causes the overestimation of the population condition in the main fishing areas. The aim of this research was to understand the spatial structuring of common hake based on the heterogeneity of biological attributes and its impact for fisheries management purposes.